The Value of Biomarkers as Predictors of Outcome in Patients with Rheumatoid Arthritis-Associated Usual Interstitial Pneumonia - Lee, Young Seok; Kim, Ho Cheol; Lee, Bo Young; Lee, Chang Keun; Kim, Mi-Young; Jang, Se Jin; Lee, Hye Sun; Moon, Jieun; Colby, Thomas V.; Kim, Dong Soon (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Because of the highly variable clinical course of rheumatoid arthritis-associated usual interstitial pneumonia (RA-UIP), the prediction of patient prognosis is important. Objective: The aim of this study was to investigate the role of blood biomarkers as prognostic predictors in the patients with RA-UIP. Methods: The blood levels of biomarkers (Krebs von den Lungen-6 [KL-6], surfactant protein-A [SP-A], matrix metalloproteinase-7 [MMP-7], interleukin-6 [IL-6], and interleukin-32 [IL-32]) were retrospectively compared with the clinical courses of 62 patients with RA-UIP. Results: The median follow-up period was 33.4 months. RA-UIP progressed in 15 patients (45.2%) during one year of follow-up. We found that KL-6 and IL-6 were significant predictors of short-term (1 year) prognosis. Multivariate logistic regression analysis showed that the odds ratio (OR) for KL-6 was 1.001 (95% confidence interval [CI]: 1.000–1.003, p = 0.077) and that the OR for IL-6 was 1.040 (95% CI: 1.002–1.080, p = 0.039) for short-term disease progression. The addition of KL-6 and IL-6 to the clinical parameters (concordance index [C-index]: 0.958, p = 0.053) predicted short-term disease progression better than the clinical parameter alone (C-index: 0.853). In addition, patients with high levels of KL-6 (≥933 U/mL) had shorter survival than those with low levels of KL-6 (